On the inducibility of cycles - Hefetz, D; Tyomkyn, M (Elsevier, 2018)
In 1975 Pippenger and Golumbic proved that any graph on n vertices admits at most 2e(n/k)k induced k-cycles. This bound is larger by a multiplicative factor of 2e than the simple lower bound obtained by a blow-up construction. Pippenger and Golumbic conjectured that the latter lower bound is essentially tight. In the present paper we establish a better upper bound of (128e/81) · (n/k)k. This constitutes the first progress towards proving the aforementioned conjecture since it was posed.